Oxide near-infrared luminescent glass-ceramics and method for preparing the same

CN116715441BActive Publication Date: 2026-11-03SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310711572.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2026-11-03
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Existing Cr3+-doped near-infrared fluorescent materials suffer from reduced luminescence efficiency during device encapsulation due to high interparticle scattering and interfacial reactions in the curing adhesive. Furthermore, the efficiency of long-wavelength near-infrared emitting materials is insufficient, making it difficult to meet the requirements for efficient excitation and broadband emission.

Method used

The long-wave emission near-infrared glass-ceramic material doped with Cr3+ is used. By changing the material's microstructure to glass-ceramic, the use of curing adhesive is avoided. Furthermore, the blue light absorption efficiency and luminescence quantum yield are improved by optimizing the chemical composition and annealing process. The emission peak is located in the range of 600-1300 nm, with a full width at half maximum (FWHM) of 221 nm.

Benefits of technology

It improves luminous efficiency and blue light absorption efficiency, and the emission spectrum covers the visible to near-infrared region. The external quantum efficiency reaches 46.7%, making it suitable for fields such as medical and food analysis. The device lifespan and emission power are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116715441B_ABST
    Figure CN116715441B_ABST
Patent Text Reader

Abstract

The application discloses a kind of Cr 3+ Doped oxide near-infrared luminescent glass-ceramics and a method for preparing the same. The near-infrared luminescent material comprises inorganic compounds, and the glass-ceramics has a general formula of A x B y C z O q D p ; wherein A is one or a combination of two or more of Na, Sr, Pb, and Cd elements; B is one or a combination of two or more of Sc, In, Ga, Al, and Ge elements; C is one or a combination of two or more of Si and Ge elements; O is an oxygen element; D is a Cr element; 1≤x≤4, 1≤y≤3, 3≤Z≤5, 11≤q≤15, and 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of luminescent materials technology, specifically relating to an oxide near-infrared luminescent glass ceramic and its preparation method. Background Technology

[0002] In recent years, near-infrared light has shown great promise in fields such as night vision lighting, security and safety, remote control and sensing, fiber optic communication, plant growth, non-destructive testing, targeted therapy, iris recognition, and food composition analysis. However, existing near-infrared light sources still fall far short of practical needs in terms of luminous efficiency and emission bandwidth. Therefore, the development of novel broadband near-infrared light sources has become a research hotspot for scholars both domestically and internationally. Among numerous design schemes, near-infrared phosphor-converted LEDs exhibit superior emission peak position, spectral bandwidth, luminous efficiency, and thermal stability. Furthermore, they possess simple structure, tunable spectrum, green and safe fabrication methods, low cost, and ease of miniaturization. They also hold promise for integration with portable devices such as mobile phones, thus being considered the most reliable broadband near-infrared light source solution.

[0003] Currently, the main ions in inorganic phosphors that can produce near-infrared emission are: Pr 3+ ,Nd 3+ ,Tm 3+ Eu 2+ Ce 3+ ,Yb 3+ Er 3+ Ho 3+ Rare earth ions and Cr 3+ Ni 2+ ,Mn 2+ Transition metal ions, including Pr. 3+ ,Nd 3+ ,Tm 3+ ,Yb 3 + Er 3+ Ho 3+ Ions emit sharp lines, which makes them unsuitable for the widespread application of near-infrared light sources; Eu 2+ ,Mn 2+ and Ce 3+ Near-infrared luminescence of Ni has only been reported in a very few systems, and a considerable portion of its emission spectrum still contains visible light; 2+ Ions typically exhibit dual-mode fluorescence in both the visible and near-infrared regions, but the latter's relatively low efficiency severely limits its feasibility as a near-infrared light source; conversely, Cr... 3+ Ions not only possess easily achievable broadband emission characteristics, but also exhibit high luminous efficiency, tunable emission spectra, and can be directly and efficiently excited by blue LEDs, making them valuable for research and promising for applications.

[0004] Currently Cr3+ Ion-doped broadband near-infrared fluorescent materials are primarily in powder form. When encapsulating them into devices, a curing adhesive must be used to fix the powder onto the blue light chip. The high scattering effect between the powder particles reduces the material's absorption efficiency for blue light. Furthermore, the curing adhesive can undergo interfacial reactions with the powder due to heat buildup during prolonged device use, thus reducing the device's luminous efficiency. Currently, some literature reports altering the material's microstructure, such as fabricating traditional phosphors into ceramic or glass-ceramic forms. These fluorescent materials with different microstructures can be directly encapsulated with blue light chips, avoiding the use of curing adhesives. Moreover, they can enhance the absorption coefficient of the powder to the excitation source, thereby improving quantum yield. For example, garnet-structured Y3Al5O 12 :Cr 3+ Ceramics can produce highly efficient near-infrared emission with a peak at 710 nm (Zheng G, Xiao W, WuH. Laser. Photonics. Rev. 2021, 15(7): 2100060.), while Gd3Al2Ga3O formed by glass crystallization and hot isostatic pressing... 12 :Cr 3+ Ceramics have even achieved near-infrared emission at 720 nm with an external quantum efficiency as high as 70.1% (Jiang H, Chen L, Zheng G. Adv. Opt. Mater 2022:2102741.). However, currently Cr... 3+ Most ion-doped broadband near-infrared fluorescent materials emit wavelengths below 900 nm. Some of these emit red light below 720 nm, which can cause a "red burst" due to human visual limitations. Therefore, high-efficiency long-wavelength near-infrared emitting materials are still in short supply. Developing novel, high-efficiency long-wavelength near-infrared fluorescent materials with higher blue light absorption coefficients that can be excited by blue LEDs is a crucial challenge for near-infrared LED luminescent materials. The development of related luminescent materials and devices is of great significance to the development of near-infrared light sources. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a Cr 3+ Doped long-wavelength emitting near-infrared glass ceramics and their preparation method. The preparation method is simple, easy to operate, has low equipment cost, and is pollution-free. The glass ceramics have stable chemical properties, significantly improved luminous efficiency compared to powders, and a higher emission peak position than infrared light. Furthermore, they can be effectively excited by ultraviolet, blue, and red LED chips.

[0006] The objective of this invention is achieved through at least one of the following technical solutions.

[0007] An oxide near-infrared luminescent material comprising an inorganic compound, wherein the chemical formula of the inorganic compound is A. x By C z O q D p ;

[0008] wherein, A is one or a combination of two or more of Na, Sr, Pb and Cd elements;

[0009] B is one or a combination of two or more of Sc, In, Ga, Al, Ge and Sb elements;

[0010] C is one or a combination of two or more of Si or Ge elements;

[0011] O is the oxygen element;

[0012] D is the Cr element;

[0013] 1≤x≤4, 1≤y≤3, 3≤z≤5, 11≤q≤15, 0<p≤0.1, and x+y+z+p=9.

[0014] Preferably, x is 2.8, 2.9, 3.0, y is 0.9, 0.98, 0.99, z is 4.0, 4.5, 5.0, q is 13.8, 14.0, 14.2, and p is 0.01, 0.02, 0.04, 0.07, 0.10.

[0015] Preferably, the B at least contains Al or Ge;

[0016] Preferably, the C is Si and Ge, and z=5.

[0017] Preferably, the crystal contained in the glass ceramic and Na2SrGe6O 14 have the same crystal structure.

[0018] Preferably, the near-infrared light emitted by the luminescent material has a wavelength range of 600-1300 nm.

[0019] Preferably, the chemical formula of the luminescent material is Cr 0.01 Na2SrGe 5.99 O 14 , which has an emission wavelength range of 600-1300 nm under excitation of 430 nm blue light, a peak value of about 820 nm, and a full width at half maximum up to 221 nm.

[0020] Preferably, by changing the microstructure form and annealing regime of the material, the luminescence quantum yield of the material can be increased from 28.3% to 46.7%.

[0021] Preferably, the luminescent material is one or a combination of two or more of single crystal, powder crystal, glass or ceramic.

[0022] The preparation method of the above-mentioned oxide near-infrared luminescent material includes the following steps:

[0023] 1) According to the general chemical formula A x B y C z O q D p Weigh the raw materials according to the stoichiometric ratio, grind and mix them to obtain a raw material mixture;

[0024] 2) Melt the mixture obtained in step 1) at high temperature and then cool it rapidly to obtain a glass precursor;

[0025] 3) The glass precursor obtained in step 2) is annealed at high temperature to obtain the oxide near-infrared luminescent material.

[0026] Preferably, in step 1), the raw materials are elemental, oxide, halide, sulfide, carbonate, borate, sulfate, phosphate or nitrate of sodium, strontium, indium, scandium, gallium, aluminum, zirconium, titanium, tin, germanium and chromium.

[0027] Preferably, in step 1), the grinding time is 3-60 min.

[0028] Preferably, in step 2), the high-temperature melting is carried out in an oxidizing, reducing, air, or inert gas environment.

[0029] Preferably, in step 2), the melting temperature is 1200-1500℃ and the melting time is 0.2-4h.

[0030] Preferably, in step 3), the annealing temperature is 750-1000℃ and the annealing time is 0.2-48h.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1) The near-infrared luminescent material of the present invention has high luminous efficiency (external quantum efficiency 46.7%), high blue light absorption efficiency (blue light absorption rate 53.3%), and a wide excitation and emission range, wherein the excitation spectrum covers the entire visible light region. It can be used as a light conversion material for near-ultraviolet-near-infrared LED chips, and is especially well matched with the most efficient commercial blue light chips.

[0033] 2) The near-infrared luminescent material of the present invention emits in the range of 600-1300nm under blue light excitation, with the main peak at around 820nm and a half-peak width of up to 221nm. These properties are superior to most near-infrared glass ceramics and can be applied in fields such as medical treatment, food analysis, and laser devices.

[0034] 3) The near-infrared luminescent material of the present invention is in the form of glass ceramic. Its chemical stability, density, thermal conductivity and luminous efficiency are superior to those of traditional phosphors. It can be encapsulated into near-infrared luminescent devices without the use of curing adhesive and blue light chip, which has a significant effect on improving the device's service life and emission power. Attached Figure Description

[0035] Figure 1 Comparative Example 1Cr 0.01 Na2SrGe 5.99 O 14 Comparison of quantum yield test results between phosphor and Example 1;

[0036] Figure 2 These are comparison images of the XRD patterns of the near-infrared fluorescent materials prepared in Examples 1, 2, 3, 6 and 7 with those of the standard cards;

[0037] Figure 3 The near-infrared fluorescent glass-ceramic Cr prepared in Example 1 0.01 Na2SrGe 5.99 O 14 Fluorescence spectrum;

[0038] Figure 4 These are quantum yield characterization diagrams of the near-infrared fluorescent glass ceramics prepared in Examples 1, 2, and 3.

[0039] Figure 5 These are quantum yield characterization diagrams of the near-infrared fluorescent glass ceramics prepared in Examples 1, 4, 6, and 7. Detailed Implementation

[0040] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available.

[0041] In this embodiment, an oxide near-infrared luminescent glass-ceramic is characterized by comprising an inorganic compound, wherein the chemical formula of the inorganic compound is A. x B y C z O q D p ;

[0042] Where A is one or more of the elements Na, Sr, Pb, and Cd;

[0043] B is one or more of the elements Sc, In, Ga, Al, Ge, and Sb.

[0044] C is one or a combination of two or more of Si or Ge elements;

[0045] O is oxygen element;

[0046] D is Cr element;

[0047] 1≤x≤4, 1≤y≤3, 3≤Z≤5, 11≤q≤15, 0<p≤0.1, and x+y+z+p=9.

[0048] x is 2.8, 2.9 or 3.0; y is 0.9, 0.98 or 0.99; Z is 4.0, 4.5 or 5.0; q is 13.8, 14.0 or 14.2; p is 0.01, 0.02, 0.04, 0.07 or 0.10; said B at least contains Ge or Al; said C is Ge and Si, and z=5. Said luminescent material is one or a combination of two or more of single crystal, powder crystal, glass or ceramic.

[0049] Example 1

[0050] The chemical composition formula of the near-infrared glass-ceramic of this example is Cr x Na2SrGe 6-x O 14 , where x=0.01. According to the stoichiometric ratio of each element in the chemical formula, Sb2O3 accounting for 0.4% of the mass of the aforementioned oxides is additionally added, high-purity powder raw materials of Na2CO3, SrCO3, Sb2O3, GeO2 and Cr2O3 are accurately weighed, placed in an agate mortar and ground for about 30 minutes to fully and uniformly mix the raw materials. The mixed raw materials are transferred to an alumina crucible, placed in a high-temperature reaction furnace under air atmosphere and melted at 1380°C for 30min, taken out rapidly at high temperature, the melt is poured onto a graphite mold preheated to 550°C and pressed into shape using a steel plate, then rapidly transferred to an annealing furnace at 550°C for annealing for about 4 hours, the glass obtained after natural cooling is annealed and crystallized in a high-temperature reaction furnace at 940°C for 6 hours and then naturally cooled, to obtain Cr 0.01 Na2SrGe 5.99 O 14 glass-ceramic, the XRD and fluorescence spectra of its precursor glass and glass-ceramic are respectively as shown in Figure 2 and Figure 3 , it can be seen from Figure 2 that the main crystalline phase of this glass-ceramic is Na2SrGe6O 14 , it can be known from Figure 3 that this glass-ceramic can perfectly match a 430nm blue light chip, and emits near-infrared light of 600-1300nm, with the main emission peak located at about 820nm, and the full width at half maximum can reach 221nm.

[0051] Comparative Example 1

[0052] The chemical formula of the near-infrared phosphor in this comparative example is Cr. x Na2SrGe 6-x O 14 Where x = 0.01. Accurately weigh high-purity powder raw materials of Na₂CO₃, SrCO₃, GeO₂, and Cr₂O₃ according to the stoichiometric ratio of each element in the chemical formula, and grind them in an agate mortar for about 30 minutes to ensure thorough mixing. Transfer the mixture to an alumina crucible and react it in an air-atmosphere high-temperature reactor at 1070℃ for 4 hours. After natural cooling, the near-infrared fluorescent powder Cr₂O₃ is obtained. 0.01 Na2SrGe 5.99 O 14 And determine its quantum yield, such as Figure 1 As shown in the figure: its absorption coefficient and external quantum efficiency are 30.9% and 28.3%, respectively; its absorption coefficient and external quantum efficiency are relatively low, while Cr with the same chemical composition... 0.01 Na2SrGe 5.99 O 14 Glass ceramics have higher absorption coefficients and external quantum efficiencies.

[0053] Examples 2-7

[0054] The chemical composition, melting temperature and time, and annealing crystallization temperature and time of Examples 2-7 are shown in Table 1; the preparation method is the same as in Example 1.

[0055] The XRD patterns of the near-infrared fluorescent glass ceramics prepared in Examples 1, 2, 3, 6, and 7 compared with those on the standard cards are shown below. Figure 2 The figure shows the main crystalline phases of the prepared glass-ceramic and Na2SrGe6O. 14 isomorphism;

[0056] Cr prepared in Examples 1-3 x Na2SrGe 6-x O 14 The quantum yield test results for glass ceramics with x = 0.01, 0.04, and 0.07 are as follows: Figure 4 As can be seen from the figure, glass ceramics have high quantum efficiency, and the higher the Cr doping concentration, the longer the emission wavelength.

[0057] The quantum yield characterization of the near-infrared fluorescent glass-ceramics prepared in Examples 1, 4, 6, and 7 is as follows: Figure 5 As can be seen from the figure, the regulation of chemical composition and annealing process has a certain impact on the quantum yield of glass ceramics.

[0058] Table 1

[0059]

[0060]

[0061] It should be understood that the above detailed description of the technical solutions of the present invention with reference to optimized embodiments is illustrative and not restrictive. It should not be considered that the specific implementation of the present invention is limited to this. For those skilled in the art, any modifications to the technical solutions described in the embodiments or equivalent substitutions of some technical features without departing from the concept of the present invention should be considered as falling within the scope of patent protection defined by the claims submitted by the present invention.

[0062] The above embodiments of the present invention are merely examples for clearly illustrating the present invention and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. An oxide near-infrared luminescent glass-ceramic, characterized in that, The chemical formula of the glass ceramic is Cr. x Na2SrGe 6-x O 14 Where x is 0.01, 0.04, or 0.07; the glass-ceramic has Na2SrGe6O 14 Type crystal structure.

2. The method for preparing the oxide near-infrared luminescent glass ceramic according to claim 1, characterized in that, Includes the following steps: (1) According to the chemical formula Cr x Na2SrGe 6-x O 14 The stoichiometric ratio of each element is determined by weighing raw materials containing Na, Sr, Ge, and Cr, and grinding and mixing them to obtain a raw material mixture; the raw materials are elemental, oxide, halide, sulfide, carbonate, borate, sulfate, phosphate, or nitrate of sodium, strontium, germanium, and chromium. (2) The mixture obtained in step (1) is melted at 1380°C for 0.5h. The melt is quickly taken out at high temperature and poured onto a graphite mold preheated at 550°C. It is then pressed into shape using a steel plate and then quickly transferred to an annealing furnace at 550°C for 4 hours. After natural cooling, a glass precursor is obtained. (3) The glass precursor obtained in step (2) is annealed and crystallized at 940°C for 6 hours to obtain the oxide near-infrared luminescent glass ceramic.

Citation Information

Patent Citations

  • Method for making transparent glass ceramics capable of realizing solar-pumped near infrared emission in greenhouse

    CN109336400A

  • Near-infrared fluorescent powder as well as preparation method and application thereof

    CN113956878A

  • Phosphor composition emitting light in infrared region in response to excited visible light and preparation method therefor

    WO2023003200A1